Digitalization intensity and extensive margins of exports in manufacturing firms from 27 EU countries: Evidence from Kernel-Regularized Least Squares regression - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2024)
The use of digital technologies like artificial intelligence, robotics, or smart devices can be expected to go hand in hand with higher productivity and lower trade costs, and, therefore, to be positively related to export activities. This paper uses firm level data for manufacturing enterprises from the 27 member countries of the European Union to shed further light on this issue by investigating the link between the digitalization intensity of a firm and extensive margins of exports. Applying a new machine-learning estimator, Kernel-Regularized Least Squares (KRLS), which does not impose any restrictive assumptions for the functional form of the relation between margins of exports, digitalization intensity, and any control variables, we find that firms which use more digital technologies do more often export, do more often export to various destinations all over the world, and do export to more different destinations.
Keywords: D22; F14; 330; Digital technologies; exports; firm level data; Flash Eurobarometer 486; kernelregularized least squares (KRLS)